IMPLEMENTASI MODEL ROLE PLAYING BERBANTU MEDIA BONEKA TANGAN UNTUK MENINGKATKAN KEMAMPUAN BERCERITA SISWA KELAS II TEMA PAHLAWANKU - Nourma Oktaviarini (Jurnal Bidang Pendidikan Dasar, 2020)
AbstractThe purpose of this research is (1) to describe the application of Role Playing models assisted by handpuppet and (2) to determine the enhanced ability of storytelling by implementing hand puppet RolePlaying models in grade II students SDN Talun 05. The method established in this study is class actionresearch (PTK) consisting of four phases: planning, implementation, observation, and reflection. Thedata collection techniques in this study have observed and test sheets. research results in pre-activityresults of students ' storytelling with an average of 356 44.5% With the need for guidance (PB) criteria.At the I-cycle I Meeting Observation model implementation of Role Playing helped hand puppet mediaacquire the final score number 49 percentage average value of 71.5% good criteria whereas in theSikulus I meeting II gained a score of 52 storytelling ability Students with an average amount of 547 to68.3% with sufficient criteria, whereas the outcome of the student storytelling ability with an average of52.8 423% of the need for guidance (PB) to cycle I The meeting II gained an average 547 amount of68.3% with sufficient criteria. Implementation of Model Role Playing assisted doll Media hand on cycle IImeeting I gained a score of 56 percentage value of 84% good criterion, on cycle II of meeting II with ascore of 60 percentage 87% criterion very good. Ability to tell students cycle II meeting I total score 598percentage 74.75% of the criteria is sufficient, while the II cycle of meeting II score 663 percentage82.87% good criterion. Based on the above data that implementation of Role Playing model assisted byhand doll can improve the storytelling skills of class II students Modern Mutiara Iman Ngunut SubDistrict Tulungagung Regency Abstrak Tujuan penelitian ini adalah (1) untuk mendeskripsikan penerapan model Role Playing berbantu media boneka tangan dan (2) untuk mengetahui peningkatan kemampuan bercerita dengan mengimplementasikan model Role Playing berbantu boneka tangan pada siswa kelas II SDN Talun 05. Metode yang ditetapkan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang terdiri empat tahapan diantaranya yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Hasil Penelitian pada pra kegiatan hasil kemampuan bercerita siswa dengan jumlah 356 rata-rata 44,5% dengan kriteria Perlu Bimbingan (PB). Pada siklus I pertemuan I hasil pengamatan implementasi model Role Playing berbantu media boneka tangan memperoleh jumlah skor akhir 49 prosentasi nilai rata-rata 71,5% kriteria Baik sedangkan pada sikulus I pertemuan II memperoleh skor 52 kemampuan bercerita siswa dengan jumlah 547 rata-rata 68,3% dengan kriteria cukup , sedangkan hasil kemampuan bercerita siswa dengan jumlah 423 rata-rata 52,8% Kriteria Perlu Bimbingan (PB) untuk siklus I pertemuan II memperoleh jumlah 547 rata-rata 68,3% dengan kriteria cukup. Implementasi penerapan model Role Playing berbantu media boneka tangan pada Siklus II pertemuan I memperoleh skor 56 prosentase nilai 84% kriteria baik, pada siklus II pertemuan II dengan skor 60 prosentase 87% kriteria sangat baik. Kemampuan bercerita siswa siklus II pertemuan I jumlah skor 598 prosentase 74,75% kriteria cukup, sedangkan siklus II pertemuan II skor 663 prosentase 82,87% kriteria baik. Berdasarkan data diatas bahwa implementasi model Role Playing berbantu boneka tangan dapat meningkatkan kemampuan bercerita siswa kelas II MI Modern Mutiara Iman Kecamatan Ngunut Kabupaten Tulungagung.